CIVIL SOCIETY IN UKRAINE: EMPIRICAL MEASUREMENTS OF PROGRAM «NATIONS IN TRANSIT» - Голуб’як, Н. Р. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article analyzes methodological tools of the program Freedom House «Nations in Transit». The dynamics of Ukraine’s transition to democracy and civil society is determined based on monitoring. The author distinguishes factors that keep the risk of a return to the less developed states. In conclusion, controversial issues of the verification assessment of the project are submitted.